Assessment of Carbon Sequestration and Income Analysis from Carbon Credit Sales in Rubber Plantations According to the Age of Rubber Trees - Rattanavijit, Urairat; Phumueang, Panadda (Journal of Advanced Development in Engineering and Science, 2026)
The purpose of this study is to evaluate the carbon sequestration of monoculture rubber trees at each age stage and to analyze the income generated from the sale of carbon credits for these trees. The study area consists of five rubber plantations located in the Na Sarn and Na Dern sub-districts, including Khuan Sri sub-district in Ban Na Sarn district and Ban Na sub-district in Ban Na Dern district. In this study, the ages of the rubber trees examined are 0-5 years, 6-10 years, 11-15 years, 16-20 years, and 21 years and older and study period an april to December 2024.The study found that the carbon sequestration for rubber trees aged 0-5 years totaled 18.87 tons of CO2 equivalent, amounting to 11,324.13 baht. For trees aged 6-10 years, the total carbon sequestration was 71.77 tons of CO2 equivalent, worth 43,063.96 baht. In the 11-15 years age group, the total was 90.48 tons of CO2 equivalent, equivalent to 54,289.43 baht. For trees aged 16-20 years, the total carbon sequestration reached 96.77 tons of CO2 equivalent, amounting to 58,061.16 baht, while for trees aged 21 years and older, it was 128.28 tons of CO2 equivalent, valued at 76,965.34 baht. Growing rubber not only generates income for farmers but also provides additional revenue from the sale of carbon credits and helps reduce carbon dioxide emissions. The study results contribute to sustainable rubber cultivation practices and promote effective economic and environmental development.